Exploring Learner Contexts and Influencing Factors in Language Learning Strategy Research: A Systematic Literature Review - Irhas Rahmat Syarif; Bambang Yudi Cahyono; Lestari Setyowati (Didaktika: Jurnal Kependidikan, 2025)
This Systematic Literature Review explores the context, internal factors, and external factors that influence the use of Language Learning Strategies (LLS) in English as a foreign language (EFL) learners. This study aims to: (1) identify EFL learner contexts that have been studied in previous LLS research, and (2) analyze the internal and external factors that influence LLS use by EFL learners in various contexts. A total of 32 empirical articles published between 2021 and 2025 were analyzed using the Systematic Literature Review procedure guided by PRISMA 2020, which includes the stages of identification, screening, eligibility, and inclusion. The literature search was conducted in the Scopus and ERIC databases using a combination of keywords related to language learning strategies, learner contexts, influencing factors, and English language learning. Inclusion criteria included empirical journal articles in English, published between 2021 and 2025, focusing on EFL learners and referring to the Oxford (1990) taxonomy. The analysis revealed variations in learner contexts across five key dimensions: culture, social, educational, identity, and learning environment. The results showed that the majority of research conducted in that year focused on young university students (N=25), in face-to-face learning (N=26), located in Asia or the Middle East. Furthermore, internal factors such as motivation (N=10), language proficiency (N=7), and learning autonomy (N=6) were more influential than external factors such as strategy training (N=6) and academic context (N=4). These findings highlight the importance of extending research to learners at lower levels of education, with more diverse cultural backgrounds, and in online or hybrid learning models, to develop more inclusive and context-appropriate language learning strategies.